Lettere di Eleonora Duse a Giuseppe e Teresa Giacosa - Biggi, Maria Ida (Drammaturgia, 2020)
Eleonora Duse first meets Giuseppe Giacosa in 1880, at her Turin debut, after the neapolitan experience and having just joined the Città di Torino Company, directed by Cesare Rossi. Very much has been written about their relationship, which lasted more than eleven years, of intense artistic collaboration between the great actress and the most popular Italian playwright of the late nineteenth century. In this essay is presented what remains of their correspondence through some unpublished or partially published documents that can light up, by little flashes, their intense and prime understanding in theatre and in life. The correspondence consists of twenty-nine letters of Eleonora to Giuseppe Giacosa, and ten addressed to his sister Teresa. These documents are difficult to interpret, since most of them are not dated and are not kept in chronological order.